Positive mental health and occupational burnout in the tourism sector in Peru - Paredes-Pérez, Marco Antonio José; Palomino-Crispin, Antonio Eleodoro; Ramírez-Arellano, Miguel Angel; Cardenas-Tapia, Victor Renzo; Ortega-Révolo, Daniela Isabel Dayan; Alania-Contreras, Rubén Darío (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The COVID-19 crisis and the political conflicts in Peru affected tourism activity, generating psychosocial risks. The objective of the study was to establish the relationship between positive mental health and occupational burnout in employees of the tourism sector in Junín. The approach was quantitative, basic type, correlational level, non-experimental design, cross-sectional descriptive correlational. The sample consisted of 384 collaborators, and the Positive Mental Health Scale and the Occupational Burnout Scale were applied. The results showed an inverse (Kendall's Tau b = -.738) and significant (p-value < .00) correlation between both variables. It is concluded that the better mental health, the less occupational burnout.